2018
DOI: 10.3390/nu10111750
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Maternal Pre-Pregnancy Body Weight and Gestational Diabetes on Markers of Folate Metabolism in the Placenta

Abstract: Dietary methyl donors, including folate, may modify the placenta and size at birth but the influence of maternal body weight has not been widely investigated. We therefore examined whether maternal or fetal folate status, together with indices of placental folate transport, were modulated by either maternal pre-pregnancy body mass index (BMI i.e., overweight: 25 ≤ BMI < 30 or obesity: BMI ≥ 30 kg/m2) and/or gestational diabetes mellitus (GD). We utilised a sub-sample of 135 pregnant women participating in the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 46 publications
0
4
0
Order By: Relevance
“…Maternal prepregnancy BMI categories at both upper and lower extremes may affect infant adverse birth outcomes in several ways. First, prepregnancy overweight and obesity usually cause metabolic abnormalities during pregnancy [such as gestational hypertension and diabetes (6, 7)] which may lead to placental abnormalities (27)(28)(29)(30)(31), and ultimately affect adverse birth outcomes. Second, excessive or poor maternal periconceptional weight status may increase the risk of abnormal growth and development of the offspring through epigenetic imprinting or methylation (32)(33)(34).…”
Section: Discussionmentioning
confidence: 99%
“…Maternal prepregnancy BMI categories at both upper and lower extremes may affect infant adverse birth outcomes in several ways. First, prepregnancy overweight and obesity usually cause metabolic abnormalities during pregnancy [such as gestational hypertension and diabetes (6, 7)] which may lead to placental abnormalities (27)(28)(29)(30)(31), and ultimately affect adverse birth outcomes. Second, excessive or poor maternal periconceptional weight status may increase the risk of abnormal growth and development of the offspring through epigenetic imprinting or methylation (32)(33)(34).…”
Section: Discussionmentioning
confidence: 99%
“…At the crucial period of epigenetic reprogramming, adverse uterine environment may influence the establishment and maintenance of methylation in mice. For example, Martino et al reported that placental mRNA abundance for the folate receptor alpha (FOLR1) and DNA methyltransferases (DNMT1) were influenced with raised BMI ( Martino et al, 2018 ). Although the mechanisms remain to be clarified, the alterations of the methylation patterns and expressions of the imprinted genes in mid-gestational placental tissues ( Ge et al, 2013a ) may influence the postnatal metabolism of offspring ( Crespi, 2019 ).…”
Section: Discussionmentioning
confidence: 99%
“…In particular, low levels of vitamin B12 and folate are associated with high BMI [40][41][42] and it is known that, despite regular folic acid supplement use, obese women retain low fasting serum folate levels and have a lower folate absorption phase compared to normal-weight women [19,43]. These observations are also seen in early, mid and late pregnancy, where obese women tend to have lower serum vitamin B12 and folate concentrations, and higher odds of vitamin B12 and folate deficiency compared to non-obese pregnant women [40,[44][45][46][47][48][49][50][51][52]. In fact, offspring of obese women have a two-fold higher risk of being born with NTDs despite maternal folic-acid supplement use [53].…”
Section: Obesity and One-carbon Metabolism During Pregnancymentioning
confidence: 99%